2017
DOI: 10.1021/acs.jpclett.7b01248
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cooperativity in Supported Spin-Crossover Metal–Organic Frameworks

Abstract: A c c e p t e d m a n u s c r i p t Molecular electronics originally proposed in the 1950s and reinvigorated by the founding proposition of Aviram and Ratner 1 has led to intense activity on the study of electronic transport through single molecules, supported by the advent of scanning tunneling microscopy (STM) and break junction setups. 2,3 More recently, molecules entered the field of spintronics, i.e. the control and manipulation of spins, 4 and gave birth to molecular spintronics, [5][6][7][8] where th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 50 publications
(114 reference statements)
0
21
0
Order By: Relevance
“…Recent theoretical work based on the experimental investigation of an Fe II ‐based organometallic compound on gold has shown that SCO can indeed be engineered on gold by using suitable ligands with the electric polarization of the surface driving the spin switching process. [ 73 ] It is based on the premise that electrostatic interactions play an important role in governing SCO phenomena and may give rise to cooperative effects—a role mainly attributed to elastic forces in bulk materials. The success of SCM 4 in retaining SCO and LIESST even on metallic surfaces like Ag and Cu underlines the importance of engineering new, chemically robust compounds.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Recent theoretical work based on the experimental investigation of an Fe II ‐based organometallic compound on gold has shown that SCO can indeed be engineered on gold by using suitable ligands with the electric polarization of the surface driving the spin switching process. [ 73 ] It is based on the premise that electrostatic interactions play an important role in governing SCO phenomena and may give rise to cooperative effects—a role mainly attributed to elastic forces in bulk materials. The success of SCM 4 in retaining SCO and LIESST even on metallic surfaces like Ag and Cu underlines the importance of engineering new, chemically robust compounds.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…A model based on interacting HS and LS domains (as opposed to HS and LS states) still yields a Gibb’s free energy similar to the S–D model 59 . Wavefunction ab initio calculations also reproduced the S–D model 57 , which has been used recently to explore the possibility of an enhanced cooperativity in surface-supported 2D metal-organic frameworks 60 . At equilibrium, the S−D model leads to the implicit equation: where Δ H and Δ S are the differences in enthalpy and entropy, respectively, between the HS and LS states; R is the universal gas constant.…”
Section: Resultsmentioning
confidence: 99%
“…Approximate density functional theory (DFT) is widely used in studying the catalytic [1][2][3][4][5][6] and materials [7][8][9][10][11][12][13] properties of openshell transition-metal complexes. 14 The well-localized d or f electrons of open-shell transition-metal centers impart unique properties but also can lead to a significant number of low-energy spin and oxidation states that are challenging to describe on equal footing using approximate electronic structure methods.…”
Section: Introductionmentioning
confidence: 99%